2019
DOI: 10.1111/nmo.13682
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin ameliorates the phenotype of newborn rats induced with mild necrotizing enterocolitis

Abstract: Background We have shown previously that an attenuated rodent model of mild necrotizing enterocolitis (NEC) increases intestinal histopathological severity grade, prevents typical developmental increases in the high‐frequency spectrum of heart rate variability (HF‐HRV), alters the nitrergic myenteric phenotype, and increases IL‐6 and IL‐1β when combined with anterior subdiaphragmatic vagotomy. The aims of the present study were to test the hypotheses that in mild NEC‐induced pups, administration of the orexige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…115 We have also shown that ghrelin, an orexigenic GI peptide, is able to attenuate the effects of mild NEC in rats, in a vagally dependent mechanism. 136 Other models also include treatments such as intragastric LPS or commensal bacteria from stool samples to determine the roles of IL-18, 137 IL-12, 137 intestinal epithelial apoptosis, 138 maternal milk, 71,72 probiotics, 139 NF-κB, 140 nitric oxide dysregulation, 42,141 and many more. Some models also include ischemia-reperfusion injury to mimic intestinal injuries occurring in NEC, 142 but these models are more controversial as the direct connection to NEC remains uncertain.…”
Section: Animal Models Of Necmentioning
confidence: 99%
“…115 We have also shown that ghrelin, an orexigenic GI peptide, is able to attenuate the effects of mild NEC in rats, in a vagally dependent mechanism. 136 Other models also include treatments such as intragastric LPS or commensal bacteria from stool samples to determine the roles of IL-18, 137 IL-12, 137 intestinal epithelial apoptosis, 138 maternal milk, 71,72 probiotics, 139 NF-κB, 140 nitric oxide dysregulation, 42,141 and many more. Some models also include ischemia-reperfusion injury to mimic intestinal injuries occurring in NEC, 142 but these models are more controversial as the direct connection to NEC remains uncertain.…”
Section: Animal Models Of Necmentioning
confidence: 99%
“…This strongly suggests that FQs might indeed decrease vagal output by blocking GABA transmission at the mNTS, rather than the DMV. Moreover, if vagal activity is suppressed following FQs we could also expect plastic changes to occur in the myenteric plexus in a similar fashion described by Meister et al in their model of Necrotizing Enterocolitis, with a pathological increase of the NANC pathway over the cholinergic pathway that caused, or resulted from a decrease of the vagal output to the GI tract [130,169].…”
Section: Discussionmentioning
confidence: 69%
“…This model led to the demonstration that breast milk protects against NEC (Barlow et al, 1974;Caplan et al, 1994), and also identified a role for nitric oxide in the pathogenesis of NEC (Nadler et al, 2000), the importance of bacterial colonization and TLR4 activation (Jilling et al, 2006), and the protective effects of beneficial commensal bacteria (Caplan et al, 1999), epidermal growth factor (Dvorak et al, 2002) and HMOs (Jantscher-Krenn et al, 2012). More-recent studies using the rat NEC model have identified mechanisms underlying intestinal barrier dysfunction (Ares et al, 2019), the protective effects of the hormone ghrelin (Meister et al, 2019), thrombomodulin (Li et al, 2019a) and fecal microbiota transplantation (Prado et al, 2019), and the deficiency of intestinal alkaline phosphatase that occurs in experimental NEC (Rentea et al, 2019), a finding that is also seen in human disease (Heath et al, 2019).…”
Section: Experimental Nec In Ratsmentioning
confidence: 99%